Aluízio Pinheiro Ferreira: Freemasonry, the 1930 Revolution and the creation of the Federal Territory of Guapore in Brazil - Ribeiro da Fonseca, Dante (2019)
The article discusses the biography of Aluizio Pinheiro Ferreira from 1897 to 1943. It emphasizes two features of his lifetime: his public activity and his Masonic affiliation, during the 1930 Revolution (1930-1945) and the secession of Brazilian Freemasonry (1927). The period culminated with the creation of the Federal Territory of Guaporé (now the state of Rondônia) in 1943, during harshest period of the government of exception (1937 to 1945), and the appointment of Aluizio Ferreira as Rondônia’s first governor.